Teaching humanization in undergraduate nursing course subjects - Vieira de Almeida, Débora; Corrêa Chaves, Eliane (Investigación y Educación en Enfermería, 2013)
<!-- [if gte mso 9]> <![endif]--> Objective. To describe teaching on humanization in the subjects included in nursing curricula in São Paulo city (Brazil). Method. Descriptive and cross-sectional study of subjects included in the curricula of all Higher Education Institutions (HEI) accredited by the Ministry of Education (Brazil) in São Paulo City. Humanization in nursing was defined as the encounter of subjectivities in and through the care act. Results. Thirteen curricula were studied, totaling 588 subjects. Although 59% contained some term related to humanization, when assessing compatibility with the definition used in the study, findings showed: 3% full compatibility, 28% partial, 62% no compatibility and, in 7% of the subjects, comparison was impossible. Conclusion. The undergraduate nursing subjects analyzed showed ambiguous intentionality as, although the majority contained some term related to humanization, only a minority was in accordance with the concept. <!-- [if gte mso 9]> Normal 0 21 false false false ES-CO X-NONE X-NONE <![endif]--><!-- [if gte mso 9]> <![endif]--><!-- [if gte mso 10]> <![endif]-->